2016
DOI: 10.1364/ao.55.007613
|View full text |Cite
|
Sign up to set email alerts
|

Stripe-shaped apertures in confocal microscopy

Abstract: We have theoretically verified that, compared with the aperture shapes of previous research, combining two stripe-shaped apertures in a confocal microscope with a finite-sized pinhole improves the axial resolution to a certain extent. Because different stripe shapes cause different effects, we also investigated the relationships among resolution, shapes, pinhole size, and the signal-to-background ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Divided aperture technique (DAT) refers to designing the shape of aperture based on the principle of angular gating. Previous studies have shown that using appropriate shape of apertures can help eliminate scattered light [1] [2]. People can control the degree of filtration by adjusting the size of the aperture.…”
Section: Introductionmentioning
confidence: 99%
“…Divided aperture technique (DAT) refers to designing the shape of aperture based on the principle of angular gating. Previous studies have shown that using appropriate shape of apertures can help eliminate scattered light [1] [2]. People can control the degree of filtration by adjusting the size of the aperture.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the field of view, optical section depth, and anti-scattering capability of a CM, a confocal microscopy imaging method based on the symmetrical lateral offset illumination and lateral offset detection has been proposed [8]. Using this method, divided aperture confocal microscopy (DACM) [9][10][11][12][13][14][15][16], confocal theta microscopy (CTM) [17][18][19][20], and dual-axis confocal microscopy (DCM) [21][22][23][24][25][26] have been developed for different requirements.…”
Section: Introductionmentioning
confidence: 99%
“…DACM partially shields the illumination and detection paths and improves the point spread function (PSF) of the microscope by using semicircular pupils in both the illumination and detection paths, thus enhancing the optical sectioning and anti-scattering capabilities [9][10][11][12][13][14][15]. Typical divided-aperture techniques used in DACM include D-shaped pupils [9][10][11][12], slit divided apertures [14], stripe-shaped apertures, and fan-shaped apertures [16].…”
Section: Introductionmentioning
confidence: 99%
“…To further improve the background rejection while not increasing the system complexity, the divided apertures can be employed in confocal microscopy, where the illumination beam passes through 1 aperture, while the detection beam passes through the other [1][2][3][4]. The pattern of the divided apertures can be various, including 2 D-shaped apertures, annular apertures [8], 1 annular and 1 circular apertures [9,10], quadrant apertures [11] and stripe apertures [12]. Therefore, by introducing the angular gating mechanism, this kind of microscopy can further reject the out-of-focus light.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, by introducing the angular gating mechanism, this kind of microscopy can further reject the out-of-focus light. The pattern of the divided apertures can be various, including 2 D-shaped apertures, annular apertures [8], 1 annular and 1 circular apertures [9,10], quadrant apertures [11] and stripe apertures [12]. Among these aperture patterns, D-shaped apertures (segments of circulars) were first implemented and can be optimized by adjusting the divider distance.…”
mentioning
confidence: 99%